Peningkatan Kinerja Guru Melalui Perencanaan Pendidikan Dimadrasah Tsanawiyah Swasta Alwasliyah 18 Tembung - Akmalia, Rizki; Arsita, Dhea; Qodri, Laila; Mahathir, Muhammad Syah; Dalimunthe, Naffa Qaila (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of the study is to find out the improvement of teacher performance, how much the improvement of teacher performance is for students. This type of research is qualitative and descriptive. The subjects of the research are the deputy principal and the teacher. Data collection was carried out through observation and interviews with all respondents. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of this study are that effective educational planning can improve teacher performance, namely the deputy principal assists teachers in planning the learning needed by students. The implementation of madrasas in improving teacher performance begins with the organization of the staff involved so that each staff does not overlap in carrying out their duties and responsibilities and runs according to their respective mandates. The challenge faced in planning education to improve teacher performance is the difference in the level of teachers' ability to use science and technology